2018
DOI: 10.3390/ijms19051432
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Activated Cl− Channel: Insights on the Molecular Identity in Epithelial Tissues

Abstract: Calcium-activated chloride secretion in epithelial tissues has been described for many years. However, the molecular identity of the channel responsible for the Ca2+-activated Cl− secretion in epithelial tissues has remained a mystery. More recently, TMEM16A has been identified as a new putative Ca2+-activated Cl− channel (CaCC). The primary goal of this article will be to review the characterization of TMEM16A, as it relates to the physical structure of the channel, as well as important residues that confer v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…This is an in vitro investigation, and the drug was not tested in in vivo animal models. Previously published work using CFTR −/- mice demonstrated only a mild pathology, which was in opposition to the observed disease in humans, and this may be due to substantial amounts of CaCC anion secretion in mice [41] , [42] . Further studies will include evaluation in human sinonasal or bronchial cells in vitro and ex vivo and assessment of RGAE-mediated effects on CF murine and rat animal models [43] , [44] .…”
Section: Discussionmentioning
confidence: 64%
“…This is an in vitro investigation, and the drug was not tested in in vivo animal models. Previously published work using CFTR −/- mice demonstrated only a mild pathology, which was in opposition to the observed disease in humans, and this may be due to substantial amounts of CaCC anion secretion in mice [41] , [42] . Further studies will include evaluation in human sinonasal or bronchial cells in vitro and ex vivo and assessment of RGAE-mediated effects on CF murine and rat animal models [43] , [44] .…”
Section: Discussionmentioning
confidence: 64%
“…Depending on the cell type, swelling-induced Ca 2+ release will activate TMEM16 proteins and CFTR (Thiele et al, 1998;Wanitchakool et al, 2016), which parallels activation of VRAC. This circumstance may explain many earlier findings, such as the overlapping Cl − channel pharmacology (Koslowsky et al, 1994;Rottgen et al, 2018;Centeio et al, 2020).…”
Section: Discussionmentioning
confidence: 75%
“…In addition, in vivo experiments showed that overexpression of CLCA1 could inhibit the proliferation and metastasis of colon cancer [31]. It has been proved that CLCA1 is closely related to TMEM16A, and CLCA1 can regulate TMEM16A to participate in the proliferation, migration and invasion of colorectal cancer cells [32][33][34]. It is well known that c-myc is a pro-oncogene and its products closely regulate cell proliferation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%